The materials selector - Waterman A. Norman; Ashby, Michael F. (London : Chapman & Hall/CRCnetBase, 1999)
Comprehensive guide to the selection and specification of engineering materials and related component manufacturing processes
System requirements: Pentium processor or higher, 16 MB RAM, 15MB free hard disk, SVGA monitor at 800 X 600, 256 colors, Windows 95, 98 or NT 4.0
Keywords: Materials